2017
DOI: 10.3390/f8060211
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome Characterization, Gene Expression Profiling and Ionic Responses of Nitraria sibirica Pall. under Salt Stress

Abstract: Nitraria sibirica Pall., a typical halophyte of great ecological value, is widely distributed in desert, saline, and coastal saline-alkali environments. Consequently, researching the salt tolerance mechanism of N. sibirica Pall. has great significance to the cultivation and utilization of salt-tolerant plants. In this research, RNA-seq, digital gene expression (DGE), and high flux element analysis technologies were used to investigate the molecular and physiological mechanisms related to salt tolerance of N. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
(85 reference statements)
1
12
0
Order By: Relevance
“…The high-affinity K + transporters (HKTs) can mediate Na + transport and Na + –K + symport, while the over-expressed Arabidopsis AtHKT1 showed high Na + in leaves and reduced accumulation in roots [52], favor our findings of higher Na + accumulation in grapevine leaf tissues as compared to root. The inhibition of Na + influx is the correlative index of cyclic nucleotide-gated ion channels CNGCs that were up-regulated in this study, which is in good agreement with the findings reported in halophyte shrub ( Nitraria sibirica ) [53]. The genetic factors that control the accumulation and transport of Cl − from root to leaf tissues or enable plants to maintain low leaf Cl − level are the critical determinant of salt stress tolerance in plants [54], while higher accumulation of Cl − was observed in roots as compared to leaves in our findings, intimating that grapevine possesses the salt tolerance mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…The high-affinity K + transporters (HKTs) can mediate Na + transport and Na + –K + symport, while the over-expressed Arabidopsis AtHKT1 showed high Na + in leaves and reduced accumulation in roots [52], favor our findings of higher Na + accumulation in grapevine leaf tissues as compared to root. The inhibition of Na + influx is the correlative index of cyclic nucleotide-gated ion channels CNGCs that were up-regulated in this study, which is in good agreement with the findings reported in halophyte shrub ( Nitraria sibirica ) [53]. The genetic factors that control the accumulation and transport of Cl − from root to leaf tissues or enable plants to maintain low leaf Cl − level are the critical determinant of salt stress tolerance in plants [54], while higher accumulation of Cl − was observed in roots as compared to leaves in our findings, intimating that grapevine possesses the salt tolerance mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…chinensis ( Gu et al, 2018 ), Kochia sieversiana ( Zhao et al, 2017 ), Nitraria sibirica Pall. ( Li et al, 2017a ), Suaeda maritima ( Gharat et al, 2016 ), Sporobolus virginicus ( Yamamoto et al, 2015 ), and Mesembryanthemum crystallinum ( Oh et al, 2015 ). In one such study, Wang et al (2015) compared the transcriptomes of H. glomeratus exposed to NaCl for 6, 12, 24, and 72 h and discovered 2,223, 5,643, 7,510 and 10,908 DEGs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The hydroponic solution was renewed every 4 days, and the pH was maintained at 6.0. The seedlings were grown in the greenhouse at 25 ± 3 °C under 14-h days/20 ± 2 °C under 10-h nights 60 .…”
Section: Methodsmentioning
confidence: 99%
“…The analysis methods of transcriptome and qPCR were referred to the author's previous published articles 60 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation